“The Bosporan Army” and “The Army on the Bosporus” in the time of Mithradates VI Eupator, King of Pontus - Mariusz Mielczarek (Fasciculi Archaeologiae Historicae)
During the reign of Mithradates VI Eupator, king of Pontus, the Cimmerian Bosporus was incorporated to the kingdom of Pontus. Detachments of the Mithradatic army were located on the Bosporus. The military forces of which the Bosporans disposed of also stayed on the Bosporus. The organization of the military forces as well as soldiers’ arms and armour are discussed. Special attention is devoted to the epigraphic material which is evidently the most important piece of evidence relating to the military history of the Bosporus of Mithradatic times